Formation of folklore art (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article talks about the stages of the emergence and formation of folk art, the problems encountered in scientific research . In addition, necessary recommendations for teaching, re-research of Uzbek folklore, scientific study of epics are discussed in detail.